Romans z Balladyną - Romaniszyn-Ziomek, Lidia (Postscriptum Polonistyczne, 2020)
The aim of the article is to interpret Ignacy Karpowicz’s novel Balladyny i romanse in the context of romantic literature. The concept of romantic irony becomes the main theme and here in this article it distinguishes, in Karpowicz’s work, the aesthetic features that are characteristic of such romantic texts as Balladyna or Beniowski by Juliusz Słowacki. The contradictions that are characteristic of romantic irony in Karpowicz’s novel exist as a process of creating and destroying, where interweaving and complicating cultures and orders result in creating a chaotic but deliberate reality. The digressive character of the novel, metaliterary reflections and selfreference, reveal the author’s attitude to the creative process as an intellectual, romantic and ironic game.